ROLE OF INNOVATIONS IN THE PROVISION OF MARKETING ACTIVITY IN SERVICE ENTITIES - Timur A. Tultaev; Irina V. Tultaeva (Статистика и экономика, 2016)
In the modern world innovation is one of the key factors determining the economic prospects of enterprises development, commodity markets, sectors of the economy and the state generally. The complete implementation of innovative technologies in marketing communicative policy of intangible enterprises contributes to the effective promotion of their services on the market and building a loyal consumer audience.